UV-B radiation reduces biocontrol ability of Clonostachys rosea against Botrytis cinerea - Costa, Lucio Bertoldo [UNESP]; Boechat Morandi, Marcelo Augusto; Stricker, Sara Marie; Bettiol, Wagner (Taylor & Francis Ltd, 2016)
There is a lack of information comparing UV-B radiation conidial sensitivity of the biocontrol agent Clonostachys rosea (Cr) and its target pathogen, Botrytis cinerea (Bc). We investigated the interactions in vitro and on strawberry leaf discs between previously selected Cr and Bc strains tolerant to UV-B radiation. Strawberry leaf discs inoculated with Bc, Cr, or combinations of both fungi were exposed to UV-B doses (2.9, 5.9, and 8.9 kJ m(-2)). Incidence and sporulation of both fungi were evaluated, and the Area Under Incidence Progress Curve (AUIPC) and Area Under Sporulation Progress Curve (AUSPC) were calculated. AUIPC and AUSPC of Cr on leaf discs were negatively correlated to increased UV-B. When inoculated alone on leaf discs, Bc was not affected by UV-B, but when inoculated with Cr the incidence and sporulation of Bc were positively correlated to UV-B radiation dose. In the absence of UV-B, Cr reduced incidence and sporulation of Bc. However, the ability of Cr to control Bc was reduced by 20% to 50% with increasing UV-B radiation. Increasing the applied concentration of Cr conidia 10-fold partially overcame the deleterious effects of UV-B on the ability of the biocontrol agent to reduce Bc sporulation in strawberry leaves. The selection of antagonists must fulfil many requirements; besides being active against the specific targeted plant pathogens, they must be cost-effective and have ecological characteristics suitable for the desired use conditions. We suggest that UV-B exposure must be taken into account during the development of bio-fungicides based on Cr.
Keywords: Climate change; ultraviolet radiation; UV-B radiation tolerance; grey mould